"Line care governs our entire world": Understanding the experience of caregivers of children with intestinal failure receiving long‐term parenteral nutrition. Issue 7 (18th February 2022) - Belza, Christina; Patterson, Catherine; Ghent, Emily; Avitzur, Yaron; Ungar, Wendy J.; Fehlings, Darcy; Stremler, Robyn; Wales, Paul W.
Abstract: Background: Children with intestinal failure (IF) receiving long‐term parenteral nutrition (PN) require significant medical care, including high‐risk procedures such as accessing a central venous catheter, with the majority provided by family caregivers in the home. This study sought to understand the experiences of family caregivers. Methods: This was a qualitative study of family caregivers of children with IF. Participants were recruited from an intestinal rehabilitation program to participate in virtual focus groups, which were recorded and transcribed. Thematic analysis was used to capture and describe experiences. Results: Thirteen caregivers providing care to 11 children participated in three virtual focus groups held between May and June 2020. Data analysis revealed five primary themes: (1) caregiving as a 24/7 commitment, (2) facing constant risk of death, (3) chronic illness creates difficult feelings and emotions, (4) effects on all aspects of family life, and (5) adapting and functioning as a family. The findings of this study pair well with the biopsychosocial model highlighting the need for multifaceted assessment and supports. Conclusion: The impact of caring for a child with IF receiving long‐term PN is significant for caregivers and their families and has implications for all aspects of their lives. A better understanding of the impact on caregivers and their coping strategies lays the groundwork for the optimization of quality of life for caregivers and their family.